ELPSA Kerangka Kerja untuk Merancang Pembelajaran Matematika - Tom Lowrie; Sitti Maesuri Patahuddin (Didaktik Matematika, 2015)
Abstract. This paper describes a framework for a mathematics lesson design called ELPSA. It is comprised of five learning components, namely: Experience, Language, Pictorial, Symbolic and Applications. This framework provides assistance for students to make sense of mathematics ideas in classrooms, through sequenced activities that draw of students personal experiences, encourage multiple forms of representation and apply mathematics knowledge to new experiences. This paper explains the theory that underpins the framework, and highlights the manner in which the respective components promote mathematics thinking. It concludes with a demonstration on how the ELPSA framework can be used in the process of designing lessons for Number PatternsKeywords: ELPSA, framework, number patterns